2020
DOI: 10.3389/fcomp.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone-Based Persuasive Technology for Physical Activity and Sedentary Behavior: A Systematic Review

Abstract: Mobile phone technology has been progressively employed in persuasive technology interventions design to promote physical activity (PA) and discourage sedentary behavior (SB). Because of the ubiquitous nature and seamless integration of mobile phones into user's daily lives, mobile phone-based persuasive technologies (PTs) have the potential to influence and change a user's behavior or attitude continuously. This paper provides a systematic review of 15 years of research (80 papers) focusing on the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In contrast, our work is entirely data-driven, analyzing the outcomes of 12 years of related literature to unveil inclusive design and evaluation recommendations. On a similar note, Matthews et al [34] and Aldenaini et al [2] published systematic reviews assessing the effectiveness of mobile-application-based interventions in motivating physical activity identifying novel research directions. However, they neither assess the effectiveness of individual persuasive strategies nor personalize their recommendations to specific user groups.…”
Section: St Reviews and Meta-analyses: Design Space Limitations And O...mentioning
confidence: 96%
“…In contrast, our work is entirely data-driven, analyzing the outcomes of 12 years of related literature to unveil inclusive design and evaluation recommendations. On a similar note, Matthews et al [34] and Aldenaini et al [2] published systematic reviews assessing the effectiveness of mobile-application-based interventions in motivating physical activity identifying novel research directions. However, they neither assess the effectiveness of individual persuasive strategies nor personalize their recommendations to specific user groups.…”
Section: St Reviews and Meta-analyses: Design Space Limitations And O...mentioning
confidence: 96%
“…Especially interventions using mobile phones and wearables, are efficacious for increasing PA and decreasing SB in different target groups (Lewis et al, 2017 ; Aldenaini et al, 2020 ). According to a recent review 79% of mobile phone-based studies reported successful outcomes and show to be especially effective in young adults (Aldenaini et al, 2020 ). Recently mobile technology has been growing dramatically as gaming devices, and mobile esports games have gained popularity (Newzoo, 2019 ).…”
Section: Opportunities In Esportsmentioning
confidence: 99%
“…Also, due to the subject's multidisciplinarity, multiple reviews from different domains (e.g., medicine, psychology) seem to neglect recommendations for designing and evaluating ST technology, thus failing to bridge the gap between theoretical foundations and practice [94,163]. Finally, some reviews that explore the design space for HBC [3,4,67,93,110,146] offer insights for extended explorations targeted by our work.…”
Section: Limitations and Open Questions In St Technology Research For...mentioning
confidence: 99%